Coastal Landscapes of the Mesolithic Human Engagement with the Coast from the Atlantic to the Baltic Sea - Schülke, Almut (Taylor & Francis, 2020)
Coastal Landscapes of the Mesolithic: Human Engagement with the Coast from the Atlantic to the Baltic Sea explores the character and significance of coastal landscapes in the Mesolithic - on different scales and with various theoretical perspectives and methodological approaches. Mesolithic people were strongly connected to the sea, with coastal areas vital for subsistence and communication across the water. This anthology includes case studies from Scandinavia, western Europe and the Baltic area, presented by key international researchers. Topics addressed include large-scale analyses of the archaeological and geological development of coastal areas, the exploration of coastal environments with interdisciplinary methods, the discussion of the character of coastal settlements and of their possible networks, social and economic practices along the coast, as well as perceptions and cosmological aspects of coastal areas. Together, these topics and approaches contribute in an innovative way to the understanding of the complexity of topographically changing coastal areas as both border zones between land and sea and as connecting landscapes. Providing novel insights into the study of the Mesolithic as well as coastal areas and landscapes in general, the book is an important resource for researchers of the Mesolithic and coastal archaeology.